Oxford Handbooks Online 2017
DOI: 10.1093/oxfordhb/9780199399314.013.20
|View full text |Cite
|
Sign up to set email alerts
|

Hope and Well-Being

Abstract: Snyder’s hope theory defines hope as a cognitively based construct that consists of two components: agency, the willpower to achieve a goal, and pathways, the perceived ability to generate ways to achieve that goal. Hope has been consistently linked to positive outcomes in many life domains, including aspects of positive mental health. This chapter reviews the literature on hope and positive aspects of mental health, including specific findings regarding the impact of hope on subjective, psychological, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Thus, hopeful survivors would be more likely to engage in more adaptive, active coping strategies and less likely to engage in maladaptive avoidance coping. Engaging in more goal-oriented cognitive processes may facilitate goal achievement in individuals, which, in turn, may contribute to their psychological and social functioning after a traumatic event (Lee & Gallagher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hopeful survivors would be more likely to engage in more adaptive, active coping strategies and less likely to engage in maladaptive avoidance coping. Engaging in more goal-oriented cognitive processes may facilitate goal achievement in individuals, which, in turn, may contribute to their psychological and social functioning after a traumatic event (Lee & Gallagher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research on relations between gender role socialization and hope is also severely limited and needs further examination. Although research indicates that men and women report no significant differences in overall hope, Chang (2003) suggested that men report greater agentic and pathways thinking than women do (Lee & Gallagher, 2018). Several studies have examined women’s experiences of gender role socialization and negative consequences for hope (see Lee & Gallagher, 2018, for review).…”
Section: Gender Role Socialization and The Positive Functioning Of Menmentioning
confidence: 99%
“…The most widely studied model of hope defines hope as a cognitive trait that represents the perceived capacity to identify pathways or strategies to achieve one's goals and the agency or motivation to pursue desired goals (Snyder, 2002). Hope is conceptualized as a resource that provides a means of coping with seemingly uncontrollable circumstances (Lee & Gallagher, 2018). Research has demonstrated that individuals high in hope (versus those low in hope) are more likely to make adaptive adjustments to life's challenges and utilize effective coping strategies in the face of hardship (Lee & Gallagher, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hope is conceptualized as a resource that provides a means of coping with seemingly uncontrollable circumstances (Lee & Gallagher, 2018). Research has demonstrated that individuals high in hope (versus those low in hope) are more likely to make adaptive adjustments to life's challenges and utilize effective coping strategies in the face of hardship (Lee & Gallagher, 2018). In this way, hope may promote increased positive affect, life satisfaction, and success while pursuing goals, particularly during times of stress.…”
Section: Introductionmentioning
confidence: 99%